2014
DOI: 10.1038/leu.2014.322
|View full text |Cite
|
Sign up to set email alerts
|

Clonal origins of ETV6-RUNX1+ acute lymphoblastic leukemia: studies in monozygotic twins

Abstract: Studies on twins with concordant acute lymphoblastic leukemia (ALL) have revealed that ETV6-RUNX1 gene fusion is a common, prenatal genetic event with other driver aberrations occurring subclonally and probably postnatally. The fetal cell type that is transformed by ETV6-RUNX1 is not identified by such studies or by the analysis of early B-cell lineage phenotype of derived progeny. Ongoing, clonal immunoglobulin (IG) and cross-lineage T-cell receptor (TCR) gene rearrangements are features of B-cell precursor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…The frequency of such cells may be low and precise identification would require the analysis of much greater amounts of primary patient material than was obtainable. The cell of origin of B-ALL has previously been considered to be a lymphoid-restricted cell but has more recently been postulated to be a multipotent progenitor, as suggested for ETV6-RUNX1- positive ALL from studies of monozygotic twins (Alpar et al, 2015), our study supports this conclusion. Sequencing of the genomic breakpoints of the EPOR rearrangements provided compelling evidence that the alterations arise from RAG-mediated recombination, and gene expression profiling demonstrates RAG expression in mouse and human progenitor cell populations, supporting acquisition of the EPOR rearrangement in a hematopoietic progenitor that then acquires additional alterations such as deletion of the CDKN2A/B tumor suppressor loci that contribute to the establishment of the leukemic clone.…”
Section: Discussionsupporting
confidence: 86%
“…The frequency of such cells may be low and precise identification would require the analysis of much greater amounts of primary patient material than was obtainable. The cell of origin of B-ALL has previously been considered to be a lymphoid-restricted cell but has more recently been postulated to be a multipotent progenitor, as suggested for ETV6-RUNX1- positive ALL from studies of monozygotic twins (Alpar et al, 2015), our study supports this conclusion. Sequencing of the genomic breakpoints of the EPOR rearrangements provided compelling evidence that the alterations arise from RAG-mediated recombination, and gene expression profiling demonstrates RAG expression in mouse and human progenitor cell populations, supporting acquisition of the EPOR rearrangement in a hematopoietic progenitor that then acquires additional alterations such as deletion of the CDKN2A/B tumor suppressor loci that contribute to the establishment of the leukemic clone.…”
Section: Discussionsupporting
confidence: 86%
“…Models of development from preleukemia to overt-leukemia have been established in ETV6-RUNX1 and hyperdiploid-ALL by comparing leukemia that occurred in monozygotic twins, or backtracking studies of archived neonatal blood samples (44,45). In this model, the initiating ETV6-RUNX1 fusion or hyperdiploidy abnormality was often acquired in utero to generate a preleukemic founder clone, the latter subsequently acquired a series of CNAs/SNVs, and eventually transformed to overt/frank ALL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cell of origin in which the initial functional impact of the fusion gene occurs has been contentious. It may lie anywhere antecedent to B precursor cells in the lineage hierarchy [57]. IgH, TCR and ETV6/RUNX1 are leukemia-specific molecular markers in E/R -positive ALL.…”
Section: Pathogenesis Of Etv6/runx1-positive Childhood Allmentioning
confidence: 99%
“…However, studies on clonal IgH and/or TCR gene rearrangements in E/R -positive ALL have demonstrated that the fetal cell type in which clonal advantage is elicited by E/R can be propagated after B-lineage commitment [25, 57, 66]. Consistent with this conclusion, retroviral transduction of the E/R fusion gene in murine and human models suggested that E/R could promote self-renewal of early B-cell precursors [25, 66].…”
Section: Pathogenesis Of Etv6/runx1-positive Childhood Allmentioning
confidence: 99%
See 1 more Smart Citation